Jesse Jackson for President '88 Rally at Warnor's Theatre - Watkins, Howard::::::::: (1988)
Jesse Jackson speaking at lectern making point with finger; seated: ???, and Ben Benevides Jesse Jackson '88 banner on curtain in background